Implementasi Etika Bisnis Islam dalam Meningkatan Penjualan Thrifting di Pasar Amahami Kota Bima - Rangga Dzikrul Rabbani; Ichwan P. Syamsuddin; Umar Sagaf (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research was conducted to find out how the implementation o Islamic business ethics can contribute to the increase in thrifting sale in Amahami Market, Bima City and what are the challenges faced b thrifting traders in implementing Islamic business ethics in Amaham Market, as well as the solutions offered. This research also use descriptive qualitative research methods with observation, interview and documentation of 15 sellers and buyers of thrifting goods in th amahami market of bima city. The results of this study indicate tha the application of Islamic business ethics in Amahami Market i proven to be able to increase consumer confidence in thrifting traders This trust arises because traders carry out honest and transparen business practices, are committed to the quality of goods and pric fairness, behave fairly and serve kindly, and have social care However, the application faces several challenges including the lac of a comprehensive understanding of Islamic Business Ethics, unfai competition between merchants, limited resources and access t training, and the challenges of local culture and traditions. In line wit these challenges, it also offers solutions to overcome them, namely b Increasing the Understanding and Awareness of Traders, providin Consumer Education and Increasing the Role of the Community, a well as the Establishment of Community-Based Market Supervisor Institutions